2022
DOI: 10.1097/qad.0000000000003159
|View full text |Cite
|
Sign up to set email alerts
|

Low hepatitis C virus-viremia prevalence yet continued barriers to direct-acting antiviral treatment in people living with HIV in the Netherlands

Abstract: van der Valk b,c , on behalf of the ATHENA observational cohort Objective: To describe hepatitis C virus (HCV)-viremia prevalence and barriers to direct-acting antiviral (DAA) treatment during unrestricted access to DAA in a nationwide cohort of people with HIV (PWH).Design: Retrospective analysis of prospectively collected data. Methods:We calculated yearly HCV-viremia prevalence as proportion of HCV RNApositive individuals ever HCV-tested. We then included HCV-viremic individuals with 1 visit during the era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, some countries have reported that HCV treatment uptake has declined since DAAs were first introduced, and those remaining to be treated are less engaged in care, reducing opportunities for HCV care. 33,34 Decreasing the time between infection and treatment and reducing loss to care are key to achieving HCV elimination. For example, in the Swiss TasP trial offering PCR-based screening to all MSM, one in three patients with a new HCV infection lacked HCV antibodies despite testing RNA positive.…”
Section: Discussionmentioning
confidence: 99%
“…However, some countries have reported that HCV treatment uptake has declined since DAAs were first introduced, and those remaining to be treated are less engaged in care, reducing opportunities for HCV care. 33,34 Decreasing the time between infection and treatment and reducing loss to care are key to achieving HCV elimination. For example, in the Swiss TasP trial offering PCR-based screening to all MSM, one in three patients with a new HCV infection lacked HCV antibodies despite testing RNA positive.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands however, this contribution will be minor. Micro-elimination in other subpopulations in the Netherlands has already been highly successful, such as people living with HIV and people with inherited bleeding disorders [12,13]. Increased efforts to find and cure HCV-viraemic individuals in other subpopulations, like migrants from high-endemic countries, PWID and incarcerated individuals, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Results: Retrieval was implemented in 45 sites in the Netherlands. Of 20,183 ever-diagnosed patients, 13,198 (65%) were known to be cured or still in care and 1,537 (8%) were LTFU and eligible for retrieval. Contact was established with 888/1,537 (58%) invited individuals; 369 (24%) had received prior successful treatment elsewhere, 131 (9%) refused re-evaluation and 251 (16%) were referred for re-evaluation.…”
mentioning
confidence: 99%
“…In addition, differences in healthcare and harm reduction provision, DAA scale-up and access (including for retreatment) and regional HCV RNA prevalence may have influenced reinfection risk [2,4,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%